Searching for unknown transfusion‐transmitted hepatitis viruses: a binational cohort study of 1.5 million transfused patients. (25th April 2018) - Edgren, G.; Hjalgrim, H.; Rostgaard, K.; Dahl, V.; Titlestad, K.; Erikstrup, C.; Wikman, A.; Norda, R.; Majeed, A.; ,
Abstract: Background: Both hepatitis B and C viruses were transmitted through blood transfusion before implementation of donor screening. The existence of additional, yet unknown transfusion transmittable agents causing liver disease could have important public health implications. Methods: Analyses were based on the Scandinavian Donations and Transfusions (SCANDAT2) database. Cox regression models were used to estimate the hazard ratio (HR) of developing chronic liver disease in recipients of blood from donors who later developed any chronic liver disease compared to recipients who received blood transfusion from healthy donors. We also studied whether the risk of liver disease was increased in patients who received units from 'high‐risk' donors, defined as donors who had a higher than expected occurrence of liver disease amongst their previous recipients. All analyses were stratified before and after 1992 to account for the effect of screening for hepatitis C virus. Results: A total of 1 482 922 transfused patients were included in the analyses. Analyses showed evidence of transfusion transmission of liver diseases before, but not after the implementation of hepatitis C virus screening in 1992, with HRs for any liver disease of 1.38 [95% confidence interval (CI), 1.30–1.46] and 0.99 (95% CI, 0.91–1.07), before and after 1992, respectively. Similarly, blood components from 'high‐risk' donors conferred increased risks before, but not after 1992. Conclusions: Our data provide no evidence for transfusion transmission of agents causing liver disease after the implementation of screening for hepatitis B and C, and suggest that if such transmission does occur, it is rare. Abstract : Click here to view the Editorial Comment by Dr. Alter